2021
DOI: 10.1002/ajhb.23565
|View full text |Cite
|
Sign up to set email alerts
|

The pace of secular changes of body measurements of children and adolescents from Kolkata (India) in the context of socioeconomic inequalities between the sexes

Abstract: Objectives: To examine the pace of secular changes of selected body measurements and proportions of children and adolescents from Kolkata (India), between 1952-1966 and 1999-2011 in the context of differences between the sexes. Methods:The study group consisted of 7753 children, adolescents and young adults (7-21 years of age) included in two series of studies (1952-1966 and 2005-2011). The measurements included: body height, sitting height, biacromial and biiliocristal diameters, as well as body mass. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Approximately 80% of an individual's growth and development is regulated by genes or biology (Jelenkovic et al, 2011), and the remaining 20% is determined by environmental factors such as living conditions, psychological stress, nutrition and diseases; however, genetic deviations cancel each other out at the population level (Blum, 2012a, 2012b; Moradi & Baten, 2005; Velez‐Grajales, 2008). Furthermore, it was demonstrated, that in patriarchal societies, such as India (Kryst et al, 2020), social factors (i.e., unequal treatment of children, depending on sex) can influence growth and development (i.e., body height) even stronger than genetics. Therefore, it is reasonable to speculate that environmental conditions related to socioeconomic factors are important for children's growth and development, rather than heredity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Approximately 80% of an individual's growth and development is regulated by genes or biology (Jelenkovic et al, 2011), and the remaining 20% is determined by environmental factors such as living conditions, psychological stress, nutrition and diseases; however, genetic deviations cancel each other out at the population level (Blum, 2012a, 2012b; Moradi & Baten, 2005; Velez‐Grajales, 2008). Furthermore, it was demonstrated, that in patriarchal societies, such as India (Kryst et al, 2020), social factors (i.e., unequal treatment of children, depending on sex) can influence growth and development (i.e., body height) even stronger than genetics. Therefore, it is reasonable to speculate that environmental conditions related to socioeconomic factors are important for children's growth and development, rather than heredity.…”
Section: Discussionmentioning
confidence: 97%
“…To maintain the homogeneity of our study, we continued to collect 2014 data from students in Shanghai and Guizhou as part of this study. According to a study on the inequality of growth and development of Indian children (Kryst et al, 2020), there are differences in the growth and development of between boys and girls, which may be influenced by social and family gender division of labor. Our study found that there were differences in physical growth and development between students in Shanghai and Guizhou.…”
Section: Discussionmentioning
confidence: 99%
“…In 25 studies, the design was cross-sectional, in one it was longitudinal. The region of origin was European in 11 studies (42%) (Godina et al, 2016;Hesse et al, 2016;Mumm et al, 2018Mumm et al, , 2021Mus alek et al, 2018;Rietsch, Eccard, & Scheffler, 2013;Rietsch, Godina, & Scheffler, 2013;Scheffler, 2011;Scheffler & Hermanussen, 2014;Stolzenberg et al, 2007;Woronkowicz et al, 2016), Latin American in 7 (27%) (Avila Chaurand et al, 2007;Avila Chaurand et al, 2007;Baya Botti et al, 2009;Guzm an de la Garza et al, 2019;Guzm an-de la Garza et al, 2017;Lizana & Hormazabal-Peralta, 2020;Navazo et al, 2020), Asian in 6 (23%) (Asif et al, 2021;Fazeli et al, 2019;Kelishadi et al, 2016;Khadilkar et al, 2018;Kryst et al, 2021;Öztürk et al, 2017), multinational in 2 (8%) (Mumm et al, 2018;Rietsch, Godina, & Scheffler, 2013), and North American in 1 (4%) (Hetherington-Rauth et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The basic observations are confirmed by the assessment of the temporal changes in most of the studied characteristics, which also allows us to verify the hypotheses. The lack of dependence of changes in body height in the studied adolescents over time indicates the disappearance of the secular trend of this feature, which still occurs in the general population of adolescents [ 15 , 16 , 29 , 30 ]. Therefore, in the light of the increase in body weight and hip circumference of men over time, as well as the size of the BMI and WHR index, as well as the increase in both circumferences among women, which also influenced the temporal changes in WHR, we consider the observed relationships to be unfavorable.…”
Section: Discussionmentioning
confidence: 99%